Review of electrospray observations and theory - Bošković, Stefan; Bugarski, Branko (Journal of Engineering & Processing Management, 2018)
While a liquid is dripping out of a capillary tube, there is a possibility to affect the characteristics of the exiting flow in certain ways. One of the ways already used is by introducing an electric field that can be used to change the average droplet diameter and the droplet size distribution. This process is called electrospraying, while the theory behind it is sometimes called electrohydrodynamics (EHD). This phenomenon has been investigated for more than a hundred years both empirically and theoretically. In this paper, a review of the available literature and the empirical and theoretical findings is presented. A new classification of the electrospray modes had to be given to include all the different modes mentioned by different authors. The necessary pieces of the equipment and their different types are also given.